Pendampingan Pelatihan Seni Baca Al- Quran di Pesantren Darussalam 2 Watukosek Gempol Pasuruan - anasro; Arindi (LPPM Universitas Yudharta Pasuruan, 2020)
This mentoring aims to provide knowledge and learning and experience directly to all students in training in the art of reading the alquran at pesantren Darussalam 2 Watukosek Gempol Pasuruan. This assistance uses PAR discharge through an explicit instruction method. The results of this assistance can improve students' understanding both in terms of theory and practice, skills in the art of reading the alquran by memorizing tausyih through explicit instruction. Process improvement is known through student activities in training and implementation of mentoring through activities, while the increase in results can be seen through the learning achievements of students in the practice of reading alquran both individually and in groups